(untitled) (Heritage, 2026)
This paper examines the suffering of the clergy of the Serbian Orthodox Church within the territory of the Archbishopric of Belgrade-Karlovci during the Second World War. The aim of the study is to analyse the complex position of the clergy under conditions of wartime destruction, occupation repression, and revolutionary violence. The research is based on the analysis of archival materials, church documentation, parish chronicles, memoir sources, and recorded oral testimonies, with a critical comparison of data from different sources. The findings indicate that the clergy were exposed to multiple forms of persecution and suffering. Some perished during the German bombing of Belgrade in April 1941 and the Allied air raids of 1944, while others were subjected to arrest, imprisonment, and internment in camps such as Banjica. A significant number of clergy members also faced ideological accusations and were executed without trial in the context of revolutionary purges. Special attention is given to the case studies of Hieromonk Emilijan (Banovački), abbot of the Monastery of Rajinovac, and Priest Branislav Marković of Umčari. Their tragic fates illustrate the mechanisms of local ideological conflicts and extrajudicial executions that marked the final years of the war and the immediate post-war period. The study concludes that the suffering of the clergy represents an important indicator of the position of the Church within the Archbishopric of Belgrade-Karlovci in the context of occupation, wartime devastation, and ideological conflicts.